Many-to-One Matching when Colleagues Matter - Pablo Revilla (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper studies many-to-one matching market in which each agents preferences not only depend on the institution that hires her, but also on the group of her colleagues, which are matched to the same institution. With an unrestricted domain of preferences the non-emptiness of the core is not guaranteed. Under certain conditions on agents preferences, we show that two possible situations in which, at least, one stable allocation exists, emerge. The first condition, called Group Togetherness, reflects real-life situations in which agents are more concerned about an acceptable set of colleagues than about the firm hiring them. The second one, Common Best Colleague, refers to markets in which a workers ranking is accepted by workers and firms present in such markets.
Keywords: C78; D71; 330; Many-to-one matching; Hedonic; Coalitions; Stability; Colleagues; Matching; Soziale Gruppe; Koalition; Arbeitsgruppe; Theorie